Providing breastfeeding techniques counseling towards improvement knowledge and practices for postpartum mother - Lathifah, May; Suparmi, Suparmi; Widiastuti, Dhias (Poltekkes Kemenkes Yogyakarta, 2024)
Incorrect breastfeeding techniques can lead to ineffective milk transfer and maternal nipple trauma, hindering successful breastfeeding. Proper positioning and attachment are essential components of effective breastfeeding. However, many new mothers, particularly primiparous women, often lack adequate knowledge and skills in these techniques. This study aimed to examine whether structured breastfeeding technique counseling could significantly improve the knowledge and breastfeeding practices among early postpartum primiparous mothers. A quasi-experimental study with a nonequivalent control group design was conducted involving 90 primiparous postpartum mothers (within 6 hours to 2 days postpartum). Participants were selected using convenience sampling and assigned to an intervention group (n = 45) and a control group (n = 45). The intervention group received structured breastfeeding technique counseling. Knowledge and practice levels were measured using validated questionnaires. Due to non-normal data distribution, the Mann–Whitney U test was used for statistical analysis. The mean knowledge score in the intervention group was significantly higher than in the control group (43.8 vs. lower value not reported; p < 0.001). Similarly, the mean practice score in the intervention group was significantly higher (45.0 vs. lower value not reported; p < 0.001), indicating a statistically significant improvement in both outcomes following the counseling intervention. counseling on correct breastfeeding techniques significantly enhances both the knowledge and practices of primiparous postpartum mothers. These findings underline the importance of integrating structured educational programs into postpartum care to support new mothers effectively.